Designing a wireless robot plotter as a supporting tool for understanding logical thinking - Aan Darmawan H; Ratnadewi Ratnadewi; Agus Prijono (Institute of Computer Science (IOCS), 2023)
OSTR stands for Open Source Turtle Robot is a turtle robot whose hardware and software are open source and published by MakersBox located in Adair Village, OR, United States of America. In this study OSTR will be developed into an Wireless Robot Plotter that can draw and write and is equipped with computer software to support the needs of the learning process in understanding logical thinking for students. In this study, a wireless Robot Plotter design has been successfully designed to support students' understanding of logical thinking. A logical thought in the form of syntactic logic steps